O processo de variação nas estruturas de tempo composto e voz passiva: avaliação das formações verbais de duplo particípio - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This work deals with the phenomenon of variation that occurs in verbal formations of double participle in compound tense and passive voice structures and aims to observe how is manifested the evaluation that bageenses speakers do in front of constructions in which the use of the double participles presents in variation. In order to do so, it was observed which forms of participle were better evaluated by the speakers in view of the lexical item linguistic factors and verbal conjugation and the extralinguistic factors of schooling, gender, age and individual. The research is based on "Variationist Sociolinguistics" or "Theory of Variation ", which has as reference the studies of the linguist Labov. As part of the theoretical basis, the dissertations of DA SILVA (2008) and MIARA (2013) were analyzed, whose results were used to compose the hypotheses presented here. The methodology used comes from the evaluation that the speakers make in the choice of the regular participle or the irregular between the verbs of double participle for the formation of sentences. These data were obtained from the application of a written test to a population composed of 16 bageenses speakers distributed between men and women, aged between 18 and 28 years and 50 and 60 years and with incomplete elementary education levels (5th to 7th grade) or full and also higher education complete or in progress. The collected data were submitted to analysis through the GOLDVARB X Program, which is part of the VARBRUL program package and provides data regarding the percentage of application of a variable rule and relative weight. What we can perceive is that in the compound time structure, with respect to the lexical item factor group, the use of the irregular participle obtained the same average of the regular form, whereas in the group of factors, the irregular participle obtained better evaluation among individuals with higher education. In the passive voice structure, the best evaluated form of participle was the irregular participle between the verbs arranged in the lexical item factor group and also among the individuals from 50 to 60 years old who corresponded to elements of the age group. With these data it was possible to arrive at a profile of the speakers of the city of Bagé who consider as best the irregular form of participle and also to understand how the evaluation of the speakers was constituted in relation to certain linguistic constructions, considering the process of variation, with emphasizes the verbal formations of double participles, although the data presented provide us with only a hint signaled by the evaluation of the use of the language.
Keywords: Letras; Tempo composto; Voz passiva; Particípios duplos; Avaliação; CNPQ::LINGUISTICA, LETRAS E ARTES